1984
DOI: 10.1002/nur.4770070210
|View full text |Cite
|
Sign up to set email alerts
|

A Patient Self‐Disclosure Instrument

Abstract: Four studies in which a patient self-disclosure questionnaire was developed and tested are reported. The instrument was designed to include only content judged by both patients and clinicians as important. Three areas of patient difficulty in disclosing to a health care provider were measured: personal problems and feelings, responses to health care, and life style. Patient difficulty in disclosure was assessed by 21 7-point rating scales, 7 for each disclosure area; ratings were summed to obtain scores. A cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…At the explicit risk of oversimplifying the choices, we assert our preference for empathic questioning over the possible perception of a “brusque confrontation” (Melton et al, , p. 92) that could negatively impact the quality of information gathered. Research in the non‐forensic clinical context supports the idea that clinical empathy helps to promote patient self‐disclosure during history taking (Dawson, Schirmer, & Beck, ).…”
Section: Empathy and Accuracy In Forensic Evaluationsmentioning
confidence: 88%
“…At the explicit risk of oversimplifying the choices, we assert our preference for empathic questioning over the possible perception of a “brusque confrontation” (Melton et al, , p. 92) that could negatively impact the quality of information gathered. Research in the non‐forensic clinical context supports the idea that clinical empathy helps to promote patient self‐disclosure during history taking (Dawson, Schirmer, & Beck, ).…”
Section: Empathy and Accuracy In Forensic Evaluationsmentioning
confidence: 88%
“…Subscale scores could range from 7 to 49. In studies (Dawson et al, 1984) to test the reliability and validity of the tool, the content areas were confirmed by factor analytic procedures, and self-disclosure scores were shown to be influenced by locus of control, specific patient expectations, and to covary with heart rate changes. High internal consistency and satisfactory test-re-test reliability were obtained for the total scale and the subscales (r = .81-.88).…”
Section: Instrumentsmentioning
confidence: 91%
“…Patient self-disclosure. To obtain a measure of how important and difficult patients thought it was to discuss with their health care provider, a 21-item patient self-disclosure questionnaire (Dawson, Schirmer, & Beck, 1984) was used. The instrument contains seven items for each of three content areas: Personal Problems and Feelings, Responses to Health Care, and Life Style.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colliver, Willis, Robbs, Cohen, and Swartz (1998), in a study using observer ratings of empathy in conjunction with medical students' clinical performance, found that empathy was related to behaviours that made the patient feel comfortable and important, and also to history taking and physical examination skills. In a study with nurses, Dawson, Schirmer, and Beck (1984) showed that self-disclosure in patients was partly related to perceived clinician empathy. Several studies (e.g., Evans, Stanley, & Burrows, 1993) have demonstrated that empathy, at least in the form of sensitivity to patients, can be taught, and many medical and nursing schools attempt to do so.…”
Section: Empathymentioning
confidence: 99%